Determinants of Farmers' Profit Margins in the Face of Climate Vulnerability in the Oases of Kanem, Chad (Sciences et Technologies pour l’Agriculture Durable, 2026)
This article aims to analyze the determinants of farmers' profit margins in the face of climate vulnerability in the oases of Kanem (Chad). A survey was conducted among 70 oasis farmers, selected randomly. Data analysis, based on a budgetary approach, was used to assess profitability. A stochastic Cobb-Douglas production function was estimated, revealing a highly significant model with a coefficient of determination (R²) of 0.64. The results show a diversity of farmers in terms of production and farming systems. Two dominant production systems and five farming systems were identified. Based on criteria of intensification, resource use, and self-consumption, a typology of producers distinguished three main types of farming systems in the oases: consumer farmers, consumer-traders, and traders. The surveys reveal that the oases of Kanem are among the areas most affected by climate change, with oasis women being the most vulnerable to its effects. These changes have led to land degradation, including decreased fertility, reduced agricultural yields, silting of the oases, and increased salinization. The analysis of costs and revenues indicates an average gross margin of 135,675 CFA francs for all crops. The econometric analysis shows that the economic profitability of the farms is determined by several factors: invested capital, the ratio of quantity sold to quantity harvested, cultivated area, labor (family and hired), and the farmers' experience. Furthermore, an adaptation and resilience strategy to climate change must be implemented, taking into account the socio-economic and environmental conditions of the producers. Actions to be undertaken should integrate these factors to improve agricultural production and the incomes of oasis farmers in Kanem